Thermal and Mechanical Fatigue in a Qe22 Magnesium Alloy Reinforced with Short Saffil Fibres - Trojanova, Zuzanka; Lukac, Pavel (Communications - Scientific letters of the University of Zilina, 2006)
Using non-destructive methods changes in the microstructure of QE22 metal matrix composites (MMC) due to thermal and mechanical cycling have been investigated. Thermal stresses induced in composites due to a considerable difference between thermal expansion coefficients of the matrix and ceramic reinforcement may create new dislocations on cooling from elevated to ambient temperature. Thermal stresses can achieve the yield stress of the matrix and micro-glide of newly created dislocations as well as their annihilation can occur. Thermodynamic processes in the matrix influence these effects.